INTEGRASI PAI DENGAN NILAI-NILAI MODERASI BERAGAMA: KIAT-KIAT MEREGENERASI POLA BERPIKIR UNTUK MEMBANGUN IDIEALITAS PEMAHAMAN KEBERAGAMAAN DALAM DUNIA PENDIDIKAN - Ahmad Ramadhan, Sayid; Hamdanah, Hamdanah; Normuslim, Normuslim (Penerbit Lafadz Jaya, 2025)
The purpose of this study is to explore strategic approaches for regenerating students' patterns of thinking through the integration of Islamic Religious Education (PAI) with the values of religious moderation, in order to build an ideal understanding of religious life within the educational context. A literature review was used as the research method, and the findings are presented descriptively. The results indicate that there are three strategies teachers can implement to regenerate students' ways of thinking teachers must demonstrate a moderate attitude when delivering and explaining PAI content, teachers can relate PAI material to relevant local wisdom that reflects the values of religious moderation, and teachers must encourage students to identify, examine, and analyze various interpretations within the context of Islamic law (shari’ah) found in the PAI curriculum.